Tatak Pilipino [episode no. 81][videorecording]. ([Quezon City ABS-CBN], 1992)
Summary: A unique display of Pilipino ways and style.
Contents: Historical rap calendar events of August (5 min.) -- Anak ng pasig song (15 min.) -- Celebrity painters (10 min.) -- Sketches (20 min.).
Credits: Hosts, Jim Paredes and Gel Santos Relos.
Keywords: Cruz, Geneva; Red, Raymund; Motion picture actors and actresses -- Philippines; Short films; Trees -- Philippines; Philippines -- History; Music